Use of Natural minerals for Water Purification from Heavy Metals; High-Dilute Sistems: Mass Transfer, Reaction and Processes - Godymchuk (Godimchuk) A. Yu. Anna Yuryevna (2005, 2005)
В фонде НТБ ТПУ отсутствует